Dispute settlement reports 2017. World Trade Organization. (Cambridge University Press, 2018)
The Dispute Settlement Reports are the WTO authorized and paginated reports in English. They are an essential addition to the library of all practicing and academic trade lawyers and needed by students worldwide taking courses in international economic or trade law. DSR 2017: Volume 3 reports on European Union - Measures Affecting Tariff Concessions on Certain Poultry Meat Products (WT/DS492) and United States - Certain Methodologies and their Application to Anti-Dumping Proceedings Involving China (WT/DS471).